DOI: 10.31274/rtd-180813-13909
|View full text |Cite
|
Sign up to set email alerts
|

Use of site specific farming systems and computer simulation models for agricultural productivity and environmental quality

Abstract: Spatio-temporal analyses of yield variability are required to delineate areas of stable yield patterns for application of precision farming techniques. Spatial structure and temporal stability patterns were studied using 1995-97 yield data for a 25-ha field located near Story City, Iowa. Com was grown during 1995-96, and soybean for 1997. The yield data were collected on nine east-west transects, consisting of 25 yield blocks per transect. In order to compare yield variability among different crops and years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…No N-treatment was applied during the soybean phase of production. More detail about experimental layout and yield data can be found in Bakhsh (1999), Jaynes et al (1999b), and Colvin (1990). Primary tillage after harvest consisted of moldboard plow in 1996 and 1997 and chisel plow in 1998.…”
Section: Site Description and Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…No N-treatment was applied during the soybean phase of production. More detail about experimental layout and yield data can be found in Bakhsh (1999), Jaynes et al (1999b), and Colvin (1990). Primary tillage after harvest consisted of moldboard plow in 1996 and 1997 and chisel plow in 1998.…”
Section: Site Description and Experimental Designmentioning
confidence: 99%
“…input to the model (table 2). The detail of these measurements can be found in Bakhsh (1999). The management data for tillage operations, planting and harvesting dates, and fertilizer applications (table 1) were also used as model inputs.…”
Section: Input Data For Rzwqmmentioning
confidence: 99%
“…Therefore, cropping systems need to be developed which can improve agricultural efficiency while meeting environmental goals. One such system has been recognized as precision farming (Bakhsh, 1999).Several studies have shown the promising potential of precision farming for economical and environmental benefits (Power et al, 1998;Blackmore, 1994;Brown and Steckler, 1995). The motive behind this technology is making use of the spatial variability of fields.…”
mentioning
confidence: 99%
“…Therefore, cropping systems need to be developed which can improve agricultural efficiency while meeting environmental goals. One such system has been recognized as precision farming (Bakhsh, 1999).…”
mentioning
confidence: 99%